Changes in cell wall neutral sugar composition and ethylene evolution as potential indicators of woolliness in cold-stored nectarine fruit - Vasilakakis, Miltiadis; Manganaris, George A. (My University, 2005)
Changes in cell wall composition during ripening of nectarine fruit (Prunus persica var nectarina, Ait. Max, cv. "Caldesi 2000") after harvest or after cold storage were investigated. Cell wall materials were prepared from nectarine fruits after harvest, after 2, 4 and 6 weeks of cold storage (0C) and after additional ripening at room temperature (20C)for 1 and 5 days, respectively. The materials were analyzed for neutral sugars and cellulose content. Incidence of chilling injury (CI) symptoms, expressed as woolliness and gaseous emissions of CO2 and ethylene evolution, were also monitored. A significant decrease in arabinose and galactose contents as the woolliness symptoms became more intense was observed. After 6 weeks of cold storage and an additional 5 days at room temperature, arabinose and galactose contents decreased up to 63 and 34%, respectively. In addition, as the cold storage period increased, a linear decrease of total neutral sugars (r = 0.9832, P < 0.01) and arabinose content (r = 0.9903, P < 0.01) after 5 days of ripening at room temperature was recorded. Furthermore, reduced ethylene production after 6-week cold storage was accompanied by intense woolliness symptoms. Inversely, respiration rate and cellulose content did not show any consistent trend during nectarine ripening after harvest or after removal from cold storage, and therefore cannot be used as indicators of CI symptoms
Keywords: Prunus; Peach; Cells; Fruit--Ripening